ANALISIS PASIEN RAWAT INAP BERDASARKAN KELAS PERAWATAN DI RSUP Dr. KARIADI SEMARANG DENGAN METODE ANTRIAN - Friska Irnas Adiyani; Sugito Sugito; Triastuti Wuryandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
Health is the right of everyone. RSUP Dr. Kariadi as one of the health service facilities has an obligation to provide service optimally to overcome the necessities and complaints of the patients. Nevertheless, the high number of patients that are not in balance with the amount of service facilities be constraints in achieving this purpose, so the patient must be entered the waiting-list or having a queuing situation. This situation happens in queuing system of the hospitalization patients at the place for registration of hospitalization patients (TPPRI) and at the care room installation of hospitalization A and B RSUP Dr. Kariadi Semarang. Therefore, it is necessary to determine the queuing system models that is appropriately with the conditions and characteristics of the queuing at TPPRI and care room that classified based on care class. So it can help in determining the decision to achieve the effective and efficient service. From the analysis result, the best queuing model for TPPRI is and for the care room that is classified based on care class are for the main class, for the first class, for second class, dan the last for third class.